Linguistic Poetics of Units Formed on the Basis of the Cosmonym Moon in the Poetry of Usman Nasir - Jurabek Yuldashev (International Journal on Integrated Education, 2022)
This article provides information on the use of the cosmonym moon in various forms, used in the poetry of Usman Nasir and carrying a poetic meaning.